Effects of Covid- 19 Pandemic on the Tourism Sector: A Case of Central Visayas, Philippines - Esguerra, James G; Esguerra, Anthony G; Arreza, Mariae Khrisna B; Español, Rosemarie Cruz (Institut Pariwisata dan Bisnis Internasional, 2023)
The pandemic underscored the risks and vulnerability of the tourism sector. The study aims to analyze the effect of the Covid-19 pandemic on the tourism sector in Central Visayas. The pandemic cases in the region, tourist arrivals, affected establishments, tourism-related businesses, and displaced workers were the key indicators that researchers looked into in this study. This study utilized a descriptive method. The investigation was carried out in Central Visayas, Philippines. Secondary data sources were used from a review of records from government agencies to descriptively analyze the effect of the Covid-19 pandemic on the tourism sector of the region. The results show that Central Visayas is among the top regions with the most Covid -19 cases reported; the high positivity rate led to stricter community quarantine protocol which affected the tourist arrival of both the local and foreign markets. The lockdown also resulted in the closure of some accommodation, f & b, and entertainment industries, leading to a massive displacement of workers in the region.